Semantic and Lexical Transformations in CrossLinguistic Poetic Translation - Karimova Ominaxon Maxmudovna; Arustamyan Y. Y (Peerian Journals Publishing, 2025)
The translation of poetry represents one of the most intricate challenges in cross-cultural literary communication, requiring the transfer of aesthetic, cultural, and emotional values across linguistic boundaries. This study examines the semantic and lexical transformations that occur when translating poetry from Russian into English, focusing on a self-produced English translation of a selected poem by Konstantin Balmont. Drawing on the frameworks of Barkhudarov, Komissarov, and Vinay & Darbelnet, the research identifies and categorizes transformation types, including adaptation, modulation, transposition, metaphorical substitution, and semantic generalization. Through parallel-text analysis, the study demonstrates how constraints of rhyme, meter, and cultural specificity necessitate creative reworking, often resulting in lexical omissions or shifts in symbolic orientation. While compensatory strategies: additional imagery and modified metaphorical framing, help preserve emotional resonance, they can alter the source text’s philosophical undertones. The findings affirm Roman Jakobson’s assertion of the inseparability of form and meaning in the poetic function, revealing that even subtle rhythmic or structural changes produce semantic shifts. By situating the analysis within established linguistic and translation theories, this research contributes to the ongoing discourse on balancing semantic fidelity with artistic equivalence in poetry translation
Keywords: poetry translation; semantic transformation; lexical transformation; adaptation